Sexual inhibition and sexual excitation in a sample of Polish women. - Krzysztof Nowosielski; Jacek Kurpisz; Robert Kowalczyk (PLoS ONE)
The contemporary concept of sexual counseling for women with sexual problems, distress, and female sexual dysfunction (FSD) includes tailored medical and/or psychological intervention. The dual control model and the Sexual Excitation/Sexual Inhibition Inventory for Women (SESII-W) are helpful for identifying risk factors and tailoring therapy for FSD. The current study aimed to (1) validate the Polish translation of the SESII-W in a sample of Polish women, and (2) verify the usefulness of the SESII-W in clinical practice. Five hundred nine white women age 18 to 55 years old (M ± SD age = 39.7 ± 11.3 years) were included in this cross-sectional study. Linguistic validation of the Polish translation of the SESII-W was first performed. A battery of tests was then used to evaluate reliability, convergent and discriminant validity, measurement invariances, and correlations between the SESII-W and other measures. Given that the original version of the SESII-W had unsatisfactory model fit, exploratory and confirmatory factor analyses were subsequently performed. Results showed a new final model that included 26 items with seven lower- and two higher-order factors and explained 58.9% of the variance in the data, with CFI = 0.93, RMSEA = 0.05 and χ2 = 693.39, p < 0.001. Cronbach's α was 0.77 for Sexual Excitation (SE) and 0.88 for Sexual Inhibition (SI) scales. A moderate negative association between SI and the presence of FSD according to Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) criteria was noted. SE was positively associated with engaging in risky sexual behaviors, Extraversion and Openness to Experiences traits, and was negatively correlated with relationship quality. Finally, age was negatively correlated with all domains of the SESII-W except Arousal Contingency. SE and SI were both lower in older women as compared to younger once. These results demonstrate that the Polish version of SESII-W shows good psychometric properties. A higher propensity for SI was associated with the presence of sexual problems, distress, and FSD, whereas a higher propensity for SE was associated with greater engagement in risky sexual behaviors and personality type. However, future studies on larger and more diverse populations are required to confirm the replicability of the factor structure of the scale.